The activity and inhibition of the food vacuole plasmepsin from the rodent malaria parasite Plasmodium chabaudi - Martins, Tiago M. (2022)
Funding Information: This work received financial support from the Biotechnology and Biological Sciences Research Council (DW), the British Council Treaty of Windsor Anglo-Portuguese Joint Research Programme (CB & AD) and by FCT/POCTI/FEDER, Project PROTINIB, POCTI/43637/99 (TM & AD).